Camu camu (Myrciaria dubia) as a possible agricultural production alternative (Revista Sistemas de Producción Agroecológicos, 2017)
This article presents the technical-agronomic aspects of the camu camu (Myrciaria dubia), and its ecology, in addition, the potential of this species as a commercial crop is analyzed, taking into account the agroecological demand of the species and the agronomic requirements to establish it as a productive system under the conditions of the foothills of the Plains, because Colombia has a great diversity of exotic fruits with a high nutritional content, native species such as the one mentioned have been considered and prioritized as alternatives in CORPOICA investigations as one of the tropical fruits with high potential for agricultural development, although in Colombia it only registers in the departments of Amazonas and Vaupés, for this reason it is important to review the information generated about the species and analyze the potential of this as a productive system for the conditions of the foothills of the Plains. The species is important for its high nutritional value, surpassing in approximately 1.5 times to acerola (Malpighiae marginata) (1790 mg/100 g), 3 times to marañon (Anacardeum occidentale) (219 mg/100 g) and 5 times to lemon (Citrus limon) (44.2 mg/100 g), compared to orange (Citrus sinensis) contains 30 times more vitamin C, 10 times more iron, 3 times more niacin, 2 times more riboflavin and 50% more phosphorus.
Keywords: fruit; vitamins; harvest; trees; food